Liposomal Irinotecan: A Review in Metastatic Pancreatic Adenocarcinoma - Frampton, James E. (Drugs, 2020)
Liposomal irinotecan (nal-IRI; Onivyde(®); also known as pegylated liposomal irinotecan) has been developed with the aim of maximising anti-tumour efficacy while minimising drug-related toxicities compared with the conventional (non-liposomal) formulation of this topoisomerase 1 inhibitor. In combination with 5-fluorouracil and leucovorin (5-FU/LV), nal-IRI is the first agent to be specifically approved for use in patients with metastatic pancreatic ductal adenocarcinoma (mPDAC) who have progressed following gemcitabine-based therapy. In the pivotal, phase III NAPOLI-1 trial, intravenous administration of nal-IRI + 5-FU/LV to gemcitabine-pretreated patients with mPDAC (as a second-line treatment in approximately two-thirds of cases) was associated with a significant ≈ 2-month median overall survival advantage compared with 5-FU/LV alone. Moreover, adding nal-IRI to 5-FU/LV extended survival with a manageable safety profile and without adversely affecting health-related quality of life, thereby producing significant and clinically meaningful gains in quality-adjusted survival relative to 5-FU/LV alone. Complementing the observed efficacy and safety of nal-IRI in NAPOLI-1 are an increasing number of real-world studies, which provide evidence of the effectiveness of this combination therapy in the treatment of mPDAC that has progressed following gemcitabine-based therapy in contemporary clinical practice in Europe, the USA and East Asia. Thus, nal-IRI, in combination with 5-FU/LV, is the first regimen specifically approved for use as a second- or subsequent-line therapy in gemcitabine-pretreated patients with mPDAC and, as such, represents a valuable treatment option in this setting.